2012
DOI: 10.1039/c2ob25107h
|View full text |Cite
|
Sign up to set email alerts
|

Peptide and peptidomimetic ligands for CXC chemokine receptor 4 (CXCR4)

Abstract: This article is dedicated to the lOth anniversary of Organic & Biomolecular Chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 157 publications
0
29
0
1
Order By: Relevance
“…However, it did not achieve maximal pharmacodynamics effect in human based on the elevation of white blood cells (28). Alternatively, many peptide antagonists have been identified for CXCR4, and include T22, T140 and its analogues, a cyclic pentapeptide FC131 and its analogues, CTCE-9908 and BKT140 (17)(18)(19). Some of them, such as CTCE-9908 and BKT140, were moved into clinic studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it did not achieve maximal pharmacodynamics effect in human based on the elevation of white blood cells (28). Alternatively, many peptide antagonists have been identified for CXCR4, and include T22, T140 and its analogues, a cyclic pentapeptide FC131 and its analogues, CTCE-9908 and BKT140 (17)(18)(19). Some of them, such as CTCE-9908 and BKT140, were moved into clinic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, many potent peptide antagonists for CXCR4 have been identified (17). However, these peptide antagonists generally have a short in vivo half-life.…”
Section: Introductionmentioning
confidence: 99%
“…Oishi et al 17 reported a compilation of different peptides and peptidomimetic ligands of CXCR4. Among them, pepducins 18 are a representative family of intracellular regulators of GPCR signaling 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have no structural resemblance with known peptide ligands and can be considered as functional (type--II) mimetics. reviewed by Oishi and Fujii [47].…”
Section: Cxcr4: Biology and Pharmacologymentioning
confidence: 99%